Precalculus : (Pearson Addison Wesley, 2006)
With a visual, graphical approach that emphasizes connections among concepts, this text helps students make the most of their study time. The authors show how different mathematical ideas are tied together through their zeros, solutions, and x-intercepts theme; side-by-side algebraic and graphical solutions; calculator screens; and examples and exercises. By continually reinforcing the connections among various mathematical concepts as well as different solution methods, the authors lead students to the ultimate goal of mastery and success in class.